Gestión de auditoría del Sistema de Gestión Ambiental NTC/ISO19011:2018 de la clínica Colsubsidio ciudad Roma - Medina Pineda, Ana María (Universidad Antonio Nariño, 2022)
This document evidences the process that was generated during the internship developed in the Colsubsidio Ciudad Roma Clinic where an audit was conducted by means of dynamic instruments, which evaluates the processes related to waste, to be executed the audit followed the guidelines indicated in the environmental management system and the integrated management plan of waste generated in health and other activities, The audit was implemented not only in the different areas of the clinic, but also to the personnel who were present at the time of the audit and through this verification, findings were found, where an analysis of the causes was generated and in this way an optimal action plan was made